2021
DOI: 10.1093/ndt/gfab176
|View full text |Cite
|
Sign up to set email alerts
|

Role of non-alcoholic fatty liver disease in the evolution of renal function in patients with diabetes mellitus

Abstract: Background Increasing prevalence in type 2 diabetes mellitus (T2DM) have influenced in an increasing prevalence of chronic kidney disease (CKD). Little is known about the influence of non-alcoholic fatty liver disease (NAFLD) on progression of CKD. The aim of this study was to analyse the role of NAFLD and its severity in the progression of renal function in patients with T2DM. Methods Retrospective and observational study, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Importantly, only hepatic steatosis is evaluated in the mentioned studies, and thus, preclusion of any association between CKD and the more severe stages of the NAFLD spectrum cannot be made by these studies. In fact, an association between fibrosis and increased risk of CKD has been suggested by several studies, the most recent study being one by Aubert et al [52]. Here, CKD progression was found to be greater in patients with type 2 diabetes with an eGFR >30 mL/min/1.73 m 2 having a high risk of hepatic fibrosis compared with those with low risk for fibrosis.…”
Section: Discussionmentioning
confidence: 79%
“…Importantly, only hepatic steatosis is evaluated in the mentioned studies, and thus, preclusion of any association between CKD and the more severe stages of the NAFLD spectrum cannot be made by these studies. In fact, an association between fibrosis and increased risk of CKD has been suggested by several studies, the most recent study being one by Aubert et al [52]. Here, CKD progression was found to be greater in patients with type 2 diabetes with an eGFR >30 mL/min/1.73 m 2 having a high risk of hepatic fibrosis compared with those with low risk for fibrosis.…”
Section: Discussionmentioning
confidence: 79%
“…Numerous studies have reported a significant association between NAFLD and CKD ( 6 , 11 14 ). Recently, a significant association between MAFLD and CKD was established in cross-sectional and cohort studies ( 16 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is the leading cause of CKD, and CKD is considered to share common metabolic risk factors with NAFLD, such as T2DM ( 6 ). The association between NAFLD and CKD is established in several epidemiological studies ( 11 15 ), two of which are based on patients with diabetes ( 11 , 12 ). The risk of CKD progression increased with the severity of NAFLD in patients with T2DM ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lanzon et al [46] recently showed that patients with severe obesity and CKD displayed significant differences in lipid signature, changes in specific amino acids and downregulation of levels of triglycerides and diglycerides when compared to obese subjects without CKD. These changes in lipid signature also play a role in the development of nonalcoholic fatty liver, a highly prevalent condition in diabetic and obese patients which has recently been proven as a key factor in the progression of diabetic kidney disease [47].…”
Section: Therapeutic Options For Obese Patients With Ckdmentioning
confidence: 99%